Pemerolehan Bahasa Pertama Dan Aktivitas Otak Pada Siswa Kelas Rendah SD - Gusti Haryani; Silvina Noviyanti; Nazurty; Yulianti Dara Putri (Didaktik : Jurnal Ilmiah PGSD STKIP Subang, 2026)
This study aims to examine first language acquisition and its relationship with brain activity in lower-grade elementary school students. The research employed a literature study method by reviewing various scientific sources, including books, journals, and previous research findings relevant to the topic. Data were analyzed using content analysis techniques through data reduction, data presentation, and conclusion drawing. The results indicate that first language acquisition in lower-grade elementary students is still in a developmental stage, characterized by vocabulary expansion, improved understanding of language structures, and enhanced communication skills. This process is strongly influenced by brain activity, particularly in areas responsible for language comprehension and production. Moreover, brain plasticity at this age allows children to acquire language more effectively through appropriate environmental stimulation. Environmental factors such as social interaction, teachers’ roles, and instructional methods also significantly contribute to students’ language development. In conclusion, first language acquisition and brain activity are closely related and mutually influential. The findings imply the importance of interactive and brain-based language learning in elementary education. Keywords: first language acquisition, brain activity, elementary students, neurolinguistics